A global picture of drought occurrence, magnitude and preparedness - Eriyagama, Nishadi; Smakhtin, Vladimir U.; Gamage, M.S.D.Nilantha (2010)
This study examines the global patterns and impacts of droughts through the mapping of several drought-related characteristics - either at a grid or a country scale. Characteristics cover various aspects of droughts from global distribution of meteorological and hydrological drought risks to social vulnerability and indices related to water infrastructure. The maps are produced by integrating a number of publicly available global datasets. The subsequent discussion of maps allows a number of policy relevant messages to be extracted. It appears that arid and semi-arid areas also tend to have a higher probability of drought occurrence. In drought years, the highest per capita loss of river flow occurs in areas that do not normally experience climate-driven water scarcity. The study illustrates that the African continent is lagging behind the rest of the world on many indicators related to drought preparedness and that agricultural economies, overall, are much more vulnerable to adverse societal impacts of meteorological droughts. Also highlighted are regions having the largest drought deficits and durations. The ability of various countries to satisfy their water needs during drought conditions is examined using storage-related indices.